2009
DOI: 10.1097/mbp.0b013e32832e0644
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training reduces the blood pressure response of older men during submaximum aerobic exercise

Abstract: Sixteen weeks of RT significantly reduces the blood pressure response and improves the cardiovascular function of older men during submaximum aerobic exercise. Therefore, RT not only increases muscular strength and hypertrophy but also provides significant cardiovascular benefits for older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
7
0
4
Order By: Relevance
“…Chronic diseases and health conditions related to CVD were categorized based on the total number reported in the sample. 31,46 Studies that reported ≥2 chronic diseases/health conditions among their sample were categorized as having "multiple chronic conditions." 32,33 Methodological quality of the studies in our sample was assessed using a modified version of the Downs and Black Checklist 47,48 (see Data S2 for the augmented checklist).…”
Section: Data Extraction and Coded Variablesmentioning
confidence: 99%
“…Chronic diseases and health conditions related to CVD were categorized based on the total number reported in the sample. 31,46 Studies that reported ≥2 chronic diseases/health conditions among their sample were categorized as having "multiple chronic conditions." 32,33 Methodological quality of the studies in our sample was assessed using a modified version of the Downs and Black Checklist 47,48 (see Data S2 for the augmented checklist).…”
Section: Data Extraction and Coded Variablesmentioning
confidence: 99%
“…Therefore, increase in muscle strength may provide reduction in muscular activation and metabolic demand for the same absolute effort. These adaptations positively reflected on the hemodynamic responses, leading to lower cardiovascular stress during a submaximal aerobic effort in older adults 30 . Additionally, RT has been shown as an important factor in the control of muscular aging and incidence of chronic-degenerative diseases, especially metabolic syndrome, since it positively reflect on insulin resistance, abdominal obesity and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…These vascular changes after the training period possibly lower SBP during aerobic exercise. In addition, 16 weeks of resistance exercise training in healthy individuals aged Correspondence: takeshi.otsuki17@gmail.com 70-80 years seems to reduce blood pressure during submaximal aerobic exercise 21) .…”
Section: Effects Of Habitual Exercise On Blood Pressure During Exercisementioning
confidence: 99%